Uji Aktivitas Antioksidan pada Minuman Thai Thea dengan metode DPPH - Rialita Lifiani; Lilik Septiana; Nurul Adzkia Ghearizky; Efilia Meirita; Resi Rizki Banjarani (LPPM Universitas Abdurrab, 2025)
Thai tea is a tea-based beverage originating from Thailand that has gained global popularity. The key benefit of tea for health lies in its bioactive compounds, especially polyphenols, which are predominantly found in tea leaves. The DPPH (1,1-diphenyl-2-picrylhydrazyl) method is a simple and widely used analytical method for measuring antioxidant activity, as it is relatively easy, fast, and inexpensive. This study aims to evaluate the antioxidant activity of Thai tea beverages using the DPPH method. The research method used is experimental with a laboratory approach. The procedure includes the preparation of a DPPH solution, determination of the maximum wavelength of DPPH, measurement of blank solution absorbance, preparation of Quercetin as a standard solution, preparation of Thai tea test samples, and data analysis. The results showed the IC50 (Inhibitory Concentration) values for Thai Tea Sippin Original (47.56 ppm), Thai Tea Chatime Original (52.23 ppm), Thai Tea Kopi Kenangan Original (50.85 ppm), Thai Tea Es Teh Original (56.66 ppm), Thai Tea Dum-dum Original (54.73 ppm), and Quercetin standard (42.05 ppm). The results indicate that Thai tea beverages have antioxidant activity categorized as strong, particularly for Sippin Original, Chatime Original, Dum-dum Original, and Kopi Kenangan Original samples, while Sippin Original and the Quercetin standard are classified as very strong. Keywords: Thai Tea, Antioxidant, DPPH